Diagnostic potential of monoclonal antibodies developed against C-terminal polypeptide of P. falciparum Histidine Rich Protein2 (PfHRP2) in malaria infected patients from India. (18th August 2017) - Verma, Reena; Chandy, Sara; Jayaprakash, N. S.; Manoharan, Anand; Vijayalakshmi, M. A.; Venkataraman, Krishnan
Abstract: Malaria, caused by Plasmodium falciparum has become a major health burden in most tropical and developing countries. P. falciparum Histidine Rich Protein2 ( Pf HRP2), which exhibits polymorphism, is being widely used as a diagnostic marker. Recently, we reported the development of monoclonal antibodies against conserved C-terminal 105 amino acids of Pf HRP2 for malaria diagnosis. Now, in this study, the diagnostic performance of two anti-C-terminal Pf HRP2 mAbs (b10c1 and Aa3c10) were evaluated with 100 blood samples from clinically identified malaria patients from seven different geographical centers in India. Sandwich ELISA, polymerase chain reaction (PCR) and statistical tools were used for the evaluation of the performance of the anti-C-terminal Pf HRP2 mAb. These mAbs detected P. falciparum (mean OD value 1.525 ± 0.56) malaria with great accuracy with no cross reactivity with P. Plasmodium vivax (mean OD value 0.285 ± 0.051) and normal healthy control samples (mean OD value 0.185 ± 0.06) in Sandwich ELISA assay. The samples which were RDT negative for P. falciparum were also reactive in Sandwich ELISA with mean OD value of (1.303 ± 0.532). The amount of Pf HRP2 antigen in the patients' blood sample was quantified and categorized into three distinct groups having the HRP2 antigen in high, intermediate and low amounts. The presence of Pfhrp 2 gene was also confirmed by PCR analysis. The sensitivity and specificity of the mAb were found to be 95 and 96% respectively. These data strongly suggest that the anti-C-terminal Pf HRP2 mAbs b10c1 and Aa3c10 have merits for improvising the existing malarial diagnostics.